Reference values of glycosylated haemoglobin and fructosamin in dogs - Beltrame, Olair Carlos; Dittrich, Rosangela Locatelli; Medeiros, Nina Cunha; Koch, Marília Oliveira; Patrício, Lia Fordiani Lenati; Castilhos, Bruno Queiroz; Pavelski, Mariana; Laskoski, Luciane Maria (Semina: Ciências Agrárias, 2014)
Glycated haemoglobin and fructosamin levels are not commonly used to diagnosis Diabetes mellitus in dogs due to a lack of reference values. To estabilish the reference values and determination methods of glycated haemoglobin and frutosamine, both male and females, healthy dogs, 2-8 years old (n=100) were used. The methodologies used were the ionic resin and the kinetic method by the reduction of blue nitrotetrazolium, respectively. Medium values of glycated haemoglobin of 5.3-7.01% and 277.52-387. 30 for fructosamin established by Brazilian Diabetes Society methods can be adopted for dogs, both males and females.